O plano municipal de segurança alimentar e nutricional do município de Cascavel - Paraná e o direito humano à alimentação adequada - Fontolan, Maria Vitoria (2022)
This master's dissertation research has as its central theme the Human Right to Adequate Food, which since 2010 has been included as a Social Right in the Federal Constitution. Even before this date, Brazil was already structuring itself for its realization, having as milestones the creation of the National System of Food Security and Nutrition and, later, the National Policy of Food Security and Nutrition. In this sense, the study objective is to analyze the Municipal Plan of Food Security and Nutrition from Cascavel city in Paraná State facing the Human Right to Adequate Food, which is the instrument that the State undertakes to fulfill the Human Right to Adequate Food. The study was carried out on the format of three articles. The first was about the development of Human Right to Adequate Food at a global, national and local level. The second sought to understand the the Human Right to Adequate Food content, through six dimensions a) physiologic/nutritional dimension; b) cultural dimension; c) gender dimension; d) information dimension; e) environmental dimension; f) ethnic-racial dimension. And the third, analyzed the Municipal Plan of Food Nutrition and Security from Cascavel city in Paraná State, based on the Human Right to Adequate Food and its structure in the country. The study was documentary through only secondary sources, laws, official documents and scientific bibliography. As for time, it was a cross-sectional study, in the period from 2020 to 2022. The results pointed that the Plan demonstrates the municipality’s commitment to fulfilling the Human Right to Adequate Food, notwithstanding it shows some fragilities with regards to the Plans of Food Security and Nutrition structure proposed by Resolution nº 9/2014 of Inter-ministerial Chamber of Food Security and Nutrition and article 19 of the Decree nº 7.272/2010, as the lack of diagnosis of Food Security and Nutrition situation. Regarding the fulfillment of the Human Right to Adequate Food content, for its realization through the proposed goals and actions, there was a commitment of the municipality in the goals formulation focused on the physiologic/nutritional, environmental and information dimensions, but there were few goals focused on gender issues and the absence of goals and actions focused at cultural and ethnic- racial dimensions.